2012
DOI: 10.4018/jksr.2012070105
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Management

Abstract: Building a knowledge-based society is widely recognized as leading to human, social and economic benefits. This paper explores the issue of using knowledge management as an instrument for the development and sustainability of this knowledge society. The paper attempts to achieve its purpose through four main integrated steps: providing a brief review of knowledge management and the knowledge society; viewing knowledge management according to the STOPE “strategy, technology, organization, people and the environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Further results found that the quality of work-life had a significant effect on ASN Performance (C.R = 3,813; P = 0,000). This result showed that more training conducted by ASN, the greater opportunity to do knowledge sharing (Dalkir, 2011). Furthermore, knowledge sharing, which was part of knowledge management, could improve the quality of work-life in the public sector (Davenport et al, 1998).…”
Section: Figure 2 Conceptual Modelmentioning
confidence: 99%
“…Further results found that the quality of work-life had a significant effect on ASN Performance (C.R = 3,813; P = 0,000). This result showed that more training conducted by ASN, the greater opportunity to do knowledge sharing (Dalkir, 2011). Furthermore, knowledge sharing, which was part of knowledge management, could improve the quality of work-life in the public sector (Davenport et al, 1998).…”
Section: Figure 2 Conceptual Modelmentioning
confidence: 99%